Hubungan Pola Makan, Gaya Hidup, Dan Dukungan Keluarga Terhadap Kejadian Anemia Pada Remaja Putri Di Madrasah Tsanawiah Tanwirian Cianjur : The Relationship Between Diet, Lifestyle, and Family Support and the Incidence of Anemia in Adolescent Girls at Madrasah Tsanawiah Tanwirian Cianjur - Wahyuni, Nita (Indonesian Scholar Journal of Nursing and Midwifery Science, 2024)
Introduction: Anemia is a nutritional problem that is widely found throughout the world which does not only occur in developing countries but also in developed countries. Young women have a ten times greater risk of suffering from anemia compared to young men. This is because young women experience menstruation every month and are in a period of growth, so they need more iron intake. The impact of the incidence of anemia in adolescents can reduce concentration and academic achievement, as well as affect productivity among adolescents. The general objective of this study was to determine the relationship between diet, lifestyle, and family support for the incidence of anemia in young women at Madrasah Tsanawiah Tanwiriah Cianjur in 2023. Methods: This study used a quantitative method with a cross-sectional study design. The total population is 176 with a sample of 64 young women. Results: The results of the univariate statistical test showed that 36 (56,3%) female students had a poor lifestyle; 50 (78,1%) had a poor diet; and 38 (59.4%) had a supportive family. The results of the bivariate analysis found that the p-values ​​of all p-value variables <α (0,05); diet (0,016); lifestyle (0,011); and family support (0,002) mean that Ho is rejected or there is a significant relationship between pattern eating, lifestyle, and family support on the incidence of anemia in young women. Discussion: This study concludes that diet, lifestyle, and family support have a significant effect on the occurrence of anemia in adolescents, the p-value of diet 0,016 evidences this; lifestyle 0,011; and family support 0,002. Suggestions from the research that has been done, the researcher tries to provide some suggestions to future researchers. With the hope that the suggestions given can be useful in further research.